O assédio moral e a precarização do trabalho: repercussões sobre a saúde do trabalhador de telemarketing - Norat, Rafael Câmara (2018)
The present master thesis investigates the harassment in the work environment and the repercussions on workers' health, has the telemarketing operators as a category of professionals analyzed, as well the precariousness of the work which these workers are submitted. The importance of research the phenomenon of precariousness is by the fact that the mutations that causes in the world of work affect society as a whole and, for the worker, can directly affect their physical and mental health. Connects bullying as a mechanism of precarious working relationship, through the intense exploitation of this class of workers, either through excessive surveillance in the workplace, by the constant collections for results or even by the high turnover and instability in employment within the telemarketing´s sector. The objective of this study is to analyze the relationship between harassment and precariousness in the work environment of the Call centers through the discourse of the workers interviewed. The current relevance of the topic is because the recent legislative approvals in Brazil that release outsourcing (Law 13,429, dated March 31, 2017) for all company activities and the recent approval of labor reform (Law No. 13.467 / 2017). This work mainly used the qualitative approach, analyzing the qualitative approach, following the methodological steps of bibliographical research, documentary and field research, through interviews with telemarketing workers. The interpretations of the results of this research showed that bullying against telemarketing operators has been increasing as corroborated by the Labor Court data, through the increase in the number of lawsuits involving these professionals and the harassment in the work environment, as well as denouncements revealed by these workers during field research.